(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The direction of "Pedagogical education" occupies a dominant place in the educational activities of our universities, is focused on the training of a new generation of teaching staff who are able to professionally, competently solve professional tasks; ready for innovation, cooperation with all participants in the educational process, the implementation of the social order of society in the transition to new standards - educational and professional.